Карандаш и Самоделкин - Постников Валентин Юрьевич (Самые лучшие стихи и сказки, 2017)
Экземпляры: ф.12 (20170920) / Инвентарный номер: 54173 / Цена: / Сис.шифр: Д / Авт.знак: П 63 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6